Electrical conductivity and somatic cell count in zebu cow’s milk - Emmanuella de Oliveira Moura (Semina: Ciências Agrárias, 2017)
Condutividade elétrica e contagem de células somáticas do leite de vacas zThe objective was to evaluate the physico-chemical composition, somatic cell count and electrical conductivity of the milk from lactating Zebu cows. For this, monthly milk samples were collected on the official milk control day intended for analysis of electrical conductivity of milk (ECM), somatic cell count (SCC) and milk composition. We used monthly data from 680 controls, from 10 Gyr and 17 Guzerat cows from a herd located in the city of São Gonçalo do Amarante/RN, from August to November 2013. Analyses of variance, mean test and Pearson correlation analysis were conducted. The levels of fat (% F), protein (% P), lactose (% L), total solids (% TS) and non-fat dry extract (% NFDE) were dependent variables for the ECM and SCC. The milk of Gyr cows for ECM, SCC, GOR, PROT, LACT, TS and NFDE were respectively, 3.88±1.18 mS/cm, 1629±2195 thousands cells/mL, 4.71±1.77%, 3.29±0.31%, 4.5±0.33%, 13.5±1.78%, 8.79±0.37%, and for the Guzerat breed 3.59±0.88 mS/cm 1356±1793 thousands cells/mL, 4.47±0.98%, 3.43±0.32%, 4.52±0.24%, 13.5 ±1.19%, 9.02±0.48%. No significant correlations between SCC and ECM characteristics were observed. However, when the correlation of each of these parameters and milk composition in different classes for each breed was analyzed, a significant correlation of the SCC was observed with the protein and lactose in Gyr, of the ECM with the lactose and SCC with total solids and fat for the Guzerat cows.